A crônica e a crônica de José Carlos Oliveira em 1968: o império do sério e do útil - Gonring, José Irmo (2015)
This study main focus is the book Diário da patetocracia – crônicas brasileiras 1968, by José Carlos Oliveira (Vitória, 1934-1986). Since there is no official status for the Brazilian crônica, we had to infer it based on a historic approach beginning with the XIX century, when Machado de Assis sketches a definition for the genre – still addressing the ancestral serial – as the marriage between the useful and the futile with the serious and the frivolous. In JCO's texts published every day in Jornal do Brasil and later collected in the aforementioned book (a posthumous work), we see an author working against the futile and the frivolous, as well as against the lyricism/intimism derived from bossa nova that characterized the crônica in the 1950s and 1960s. The social tension of that era would find a José Carlos Oliveira always ready, in his daily column, to address relevant topics in a serious and persuasive way, making it even difficult for us to call some of his texts “crônicas”. As a man of his time, in “situation”, openly existentialist, he answers those requests with a sartrean “commitment”. In order to understand the author's attitude, we resort to Bakhtin's concept of Architectonics of Answerability. We propose that it is possible to connect these two perspectives in order to identify the dynamics governing the individuals' ethical attitudes. In the examined texts from 1968, our evaluation is that the ethical dimension overlaps the aesthetical one.